Fuzzy Logic, Artificial Neural Network, and Adaptive Neuro-Fuzzy Inference Methodology for Soft Computation and Modeling of Ion Sensing Data of a Terpyridyl-Imidazole Based Bifunctional Receptor - Sahoo, Anik; Baitalik, Sujoy (Frontiers in Chemistry, 2022)
Graphical Abstract